Schism – and Reformed theology? - Smit, Dirk J. (Acta theologica, 2021)
The article deals with the question of schism in the Reformed faith and ecclesiology, by focusing on four fundamental issues developed in the form of five theses each. These fundamental issues involve, first, the wellknown Reformed passion for the unity and catholicity of the church; secondly, the equally widely known traditional Reformed problems and troubling experiences with questions of unity and catholicity; thirdly, some typically Reformed theological perspectives on unity and catholicity as their contribution to ecumenical thought and practice, and, finally, some concrete and urgent practical challenges currently facing the Reformed faith and world community regarding unity and catholicity.